2021
DOI: 10.3389/fgene.2021.650102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a MicroRNA Signature Associated With Lymph Node Metastasis in Endometrial Endometrioid Cancer

Abstract: BackgroundLymph node metastasis (LNM) is an important prognostic factor in endometrial cancer. Anomalous microRNAs (miRNAs) are associated with cell functions and are becoming a powerful tool to characterize malignant transformation and metastasis. The aim of this study was to construct a miRNA signature to predict LNM in endometrial endometrioid carcinoma (EEC).MethodCandidate target miRNAs related to LNM in EEC were screened by three methods including differentially expressed miRNAs (DEmiRs), weighted gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…60 These results are intriguing as ascribe a role to the miR-34 family in the EC landscape. Recently, its involvement has been also supported by additional evidences 61 model and the molecular classification. 64 This aspect reflects the prognostic ability of this model and paves the way for a further ment of the current TCGA classification scheme.…”
Section: Mirnas Associated With Stage and Grade In Ecmentioning
confidence: 80%
See 1 more Smart Citation
“…60 These results are intriguing as ascribe a role to the miR-34 family in the EC landscape. Recently, its involvement has been also supported by additional evidences 61 model and the molecular classification. 64 This aspect reflects the prognostic ability of this model and paves the way for a further ment of the current TCGA classification scheme.…”
Section: Mirnas Associated With Stage and Grade In Ecmentioning
confidence: 80%
“… 60 These results are intriguing as ascribe a role to the miR‐34 family in the EC landscape. Recently, its involvement has been also supported by additional evidences 61 ; Fu et al analyzed the TCGA—UCEC (Uterine Corpus Endometrial Carcinoma) database with the aim to construct a miRNA signature able to predict LNM. The authors retrieved the data of 324 patients and identified 113 miRNAs differently expressed between the two sets of patients (ie, with and without LNM).…”
Section: Mirnas In Ecmentioning
confidence: 99%
“…Table 3 summarizes the above data. [128] miR-107-5p [68] miR-429 [129,130] miR-501 [131] miR-576-5p [132] Downregulation miR-24b-5p [133] miR-26a-5p [82] miR-34a [65,66] miR-34b-5p [134] miR-34c-3p [134] miR-34c-5p [134] miR-148b [71] miR-204-5p [126] miR-505 [135] 2.2.5. The Impact of miRNA Changes on Survival and Recurrence in Patients with Endometrial Cancer Mortality related to endometrial cancer continues to increase [136].…”
Section: Involvement Of the Lymph Nodes Metastasismentioning
confidence: 99%